2012
DOI: 10.1002/hed.23169
|View full text |Cite
|
Sign up to set email alerts
|

Identification of upregulated genes in oral squamous cell carcinomas

Abstract: The ORESTES data mining analysis indicated 40 upregulated genes in HNSCC. Nine of these candidate genes were selected for further qRT-PCR validation and 3 of them (ALDOA, AHSA1, and POLQ) were frequently found upregulated in OSCC samples, which may indicate an association of these genes with the carcinogenesis process in this tumor site and they can constitute potential new targets for therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 30 publications
(56 reference statements)
1
25
0
Order By: Relevance
“…Another report of POLQ expression in early breast cancer found the highest POLQ expression in ER negative and high-grade tumors; higher expression was correlated with shorter relapse-free survival times [83]. POLQ is one of the genes frequently upregulated in a group of oral squamous cell carcinomas from Brazil [84]. In a study of early to mid-stage non small-cell lung cancers, higher expression of a five-gene prognostic signature including POLQ was associated with poor outcome [85].…”
Section: Polq and Cancermentioning
confidence: 99%
“…Another report of POLQ expression in early breast cancer found the highest POLQ expression in ER negative and high-grade tumors; higher expression was correlated with shorter relapse-free survival times [83]. POLQ is one of the genes frequently upregulated in a group of oral squamous cell carcinomas from Brazil [84]. In a study of early to mid-stage non small-cell lung cancers, higher expression of a five-gene prognostic signature including POLQ was associated with poor outcome [85].…”
Section: Polq and Cancermentioning
confidence: 99%
“…Although overexpression ALDOA has been discovered in many tumors [9], the ultimate mechanisms are undetermined and discordant. It has been assumed that ALDOA expression increased because glycolysis is faster in rapidly evolving tumor cells than in normal tissues as an enzyme [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, data mining has been widely used in the medical assessment of various cancer types. For instance, Roberta et al found 40 genes that are up-regulated in HNSCC using ORESTES data mining analysis [12]. Zainab Abu Bakar et al constructed a framework for the diagnosis of the tumor stage of primary oral cancer by using data mining of Bayesian reasoning [13].…”
Section: Introductionmentioning
confidence: 99%